The Sound inside the Silence Travels in the Sonic Imagination - Street, Seán.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Palgrave Macmillan, 2019)
In this poetic exploration of the auditory imagination, the third in his series on sonic aesthetics, Seán Street peoples silence with sound, travelling through time and space to the distant past, the infinite future and the shadow lands of the inner psyche. Our mind is a canvas on which the colours of the sound world leave permanent impressions. It is the root of all listening.
1 Silence Awaiting Sound: the Space of the Imagination -- 2 Fencing the Horizon: Sound as an Imaginative Event -- 3 The Sounds the Ghosts Knew: Imaginative Remembering of the Past -- 4 The Music of Where We Are: How Place Shapes Sound -- 5 Through Storm and Stone: Radio, Sound and the Imagined World -- 6 Sounds of Shadows and Light: Science Fiction and the Supernatural -- 7 Remembered Voices, Pictured Lives: the Sound of Recollection -- 8 The Singing of Statues: How Art Sounds -- 9 Writing Aloud: The Sound of Voices on Page and Screen -- 10 Full of Noises: The Sound Map of Self.
Keywords: Mass media; Science -- Social aspects; Communication; Culture -- Study and teaching; Media Sociology; Science and Technology Studies; Media and Communication; Cultural Studies